Automated solid-phase extraction method for the determination of atovaquone in plasma and whole blood by rapid high-performance liquid chromatography. - Lindegårdh, N; Bergqvist, Y (2000)
A bioanalytical method for the determination of atovaquone in plasma and whole blood by solid-phase extraction and high-performance liquid chromatography has been developed and validated. A structurally similar internal standard was added and protein was precipitated from plasma and whole blood with acetonitrile before being loaded on to a C8 solid-phase extraction column. Atovaquone and internal standard were analysed by high-performance liquid chromatography on a C18 J'Sphere ODS-M80 (150x4.0 mm) column with mobile phase acetonitrile-phosphate buffer, 0.01 M, pH 7.0 (65:35, v/v) and UV detection at 277 nm. The intra-assay precisions for plasma and whole blood were 2.2% and 1.9% respectively at 12 microM and 6.0% and 5.6% respectively at 0.75 microM. The inter-assay precisions for plasma and whole blood were 1.4% and 2.1% respectively at 12 microM and 4.9% and 3.4% respectively at 0.75 microM. The lower limit of quantification in plasma and whole blood were 150 nM. The limit of detection in plasma and whole blood were 30 nM.